Skilled immigration frictions as a barrier for young firms - Federico S. Mandelman; Mishita Mehra; Hewei Shen (Federal Reserve Bank of Atlanta, 2024)
This paper studies the impact of skilled immigration policy frictions in the United States on technology-intensive firms by age cohorts. We use firm-level data and a general equilibrium model with endogenous firm entry and exit. The empirical results show that skilled immigration policy frictions directly influence young firm dynamics in technology-intensive sectors by affecting firm survival. Our general equilibrium model incorporates skilled foreign labor and immigration policy frictions that mimic the H-1B policy and matches the age distribution of firms in high-technology sectors, showing also that increased entry of younger firms leads to a greater exit of older firms.
Keywords: F22; M13; 330; skilled immigration; start-ups; high-technology firms; firm dynamics